1999
DOI: 10.1074/jbc.274.29.20603
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Conserved cis-Elements and Transcription Factors Required for Sterol-regulated Transcription of Stearoyl-CoA Desaturase 1 and 2

Abstract: We previously identified stearoyl-CoA desaturase 2 (SCD2) as a new member of the family of genes that are transcriptionally regulated in response to changing levels of nuclear sterol regulatory element binding proteins (SREBPs) or adipocyte determination and differentiation factor 1 (ADD1). A novel sterol regulatory element (SRE) (5-AGCAGATTGTG-3) identified in the proximal promoter of the mouse SCD2 gene is required for induction of SCD2 promoter-reporter genes in response to cellular sterol depletion (Tabor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
162
4
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(179 citation statements)
references
References 47 publications
12
162
4
1
Order By: Relevance
“…1 and 5). These data suggested that the induction of SCD1 and other lipogenic genes is dependent on SREBP-1c expression and would be consistent with published reports (32)(33)(34). However, using SREBP-1cϪ/Ϫ mice, we found that, unlike in short term feeding (data not shown), the long term feeding of fructose induced SCD1, ACC, and FAS mRNA to levels comparable to the levels induced by fructose in the wild-type mice (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…1 and 5). These data suggested that the induction of SCD1 and other lipogenic genes is dependent on SREBP-1c expression and would be consistent with published reports (32)(33)(34). However, using SREBP-1cϪ/Ϫ mice, we found that, unlike in short term feeding (data not shown), the long term feeding of fructose induced SCD1, ACC, and FAS mRNA to levels comparable to the levels induced by fructose in the wild-type mice (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…In a minor pathway, oleate mediates the induction of SREBP-1c expression and maturation, which in turn induces the expression of lipogenic genes consistent with published reports (34 -39, 57, 60, 61). SREBP-1c in a feedback loop can induce SCD1 gene expression by its capacity to bind to the sterol regulatory element present in the SCD promoter (32,33), resulting in the production of more oleate. As a major pathway, oleate mediates maximum induction of lipogenic gene expression by fructose in an SREBP-1c-independent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol was from steraloids and oxysterols from Sigma. The sources of all other reagents and plasmids have been given (41,42).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, adipocyte determination and differentiation factor 1/sterol regulatory elementbinding protein 1 (ADD1/SREBP1), a member of the bHLH (basic region/helixloop-helix domain protein) family, is known to induce genes implicated in the FA metabolism (e.g., types 1 and 2 stearoylCoA desaturase genes) by binding on specific DNA binding sites, such as the E-box, a helix-loop-helix consensus sequence, and the sterol response element [51,69,228,237]. A model of action for C/EBPs, PPARγ and ADD1/SREBP1 has been proposed [69,156].…”
Section: The Early and Late Adipocyte Differentiationmentioning
confidence: 99%